1987
DOI: 10.1017/s0043174500079418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Imazaquin for Weed Control in Flue-Cured Tobacco (Nicotiana tabacum)

Abstract: Imazaquin {2-[4,5-dihydro-4-methyl-4-(1-methylethyl)-5-oxo-1H-imidazol-2-yl]-3-quinolinecarboxylic acid} was evaluated in the field for weed control in flue-cured tobacco (Nicotiana tabacumL.) during 1983 and 1984. The 75 DG formulation of imazaquin was used at 0.28 and 0.42 kg ai/ha. Methods of application were: preplant incorporated, over the top immediately after transplanting, postbed incorporated, and early postemergence. Imazaquin controlled 90%, or better, of common lambsquarters (Chenopodium albumL. # … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 2 publications
1
12
1
Order By: Relevance
“…In all years, there were few differences in price among herbicide treatments, regardless of application method. In other research, Walls et al (1987) found few differences in the quality of tobacco among herbicide treatments, and differences in gross monetary returns occurred only when severe injury reduced yields.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…In all years, there were few differences in price among herbicide treatments, regardless of application method. In other research, Walls et al (1987) found few differences in the quality of tobacco among herbicide treatments, and differences in gross monetary returns occurred only when severe injury reduced yields.…”
Section: Resultsmentioning
confidence: 73%
“…Most herbicides registered for use in tobacco control annual grasses. Previous research evaluated broadleaf weed control in tobacco with herbicides such as imazaquin (Hagood and Komm 1987;Walls et al 1987) and fomesafen (Bridges and Stephenson 1991). Effective weed control was observed; however, neither herbicide was registered due to potential tobacco injury.…”
Section: Introductionmentioning
confidence: 99%
“…No herbicides are currently registered for postemergence broadleaf weed control in dark tobacco. Previous research with broadleaf herbicides such as imazaquin (Hagood and Komm 1987;Walls et al 1993) and fomesafen (Bridges and Stephenson 1991) showed effective weed control but unacceptable tobacco injury.…”
mentioning
confidence: 92%
“…), common ragweed, and sicklepod (Cassia obtusifolia L.). The influence of these weeds on tobacco yield and quality has been documented (4,15,18).…”
Section: Introductionmentioning
confidence: 99%
“…1993. Volume 7:370-375 WEED TECHNOLOGY cation except PPI (15). The objective of this study was to investigate the effects of application methods on the absorption, translocation, and metabolism of imazaquin in field-grown, flue-cured tobacco.…”
mentioning
confidence: 99%